Pengaruh Berbagai Jenis Media Tanam dan Konsentrasi Asam Amino Terhadap Pertumbuhan Stek Kopi Robusta (Coffea canephora L.) - Himawan Daffa Harsantyo; Anni Nuraisyah; Abdul Madjid; Setyo Andi Nugroho; Triono Bambang Irawan; Titien Fatimah (Jurnal Javanica, 2025)
Furthermore, by providing amino acids, robusta coffee cuttings can get nutrients to promote the growth of vegetative organs. The purpose of this study was to examine the effects of various growing media types, amino acid combinations, and their interactions on the growth of robusta coffee (Coffea canephora L.) cuttings. Growing medium was the first component, and amino acids were the second in this factorial randomized group design (RCBD) investigation. In this study, a variety of media were employed as the growth medium. Subgrade soil, sand, and blotong fertilizer made up P1 media; subgrade soil, sand, and coffee husk compost made up P2 media; and subgrade soil, sand, and chicken manure fertilizer made up P3 media (2:1:1). 108 experimental units of the amino acids U0: 0%, U1: 5%, U2: 10%, and U3: 15% were employed in this investigation. The planting media treatment significantly affected the root volume, root wet weight, and root dry weight characteristics with the P2 treatment. The best materials were sand, coffee husk compost, and topsoil. The A1 (5%) treatment was the best; all other metrics were impacted by the amino acid treatment, with the exception of the cutting growth percentage.